2021
DOI: 10.1096/fj.202002557rr
|View full text |Cite
|
Sign up to set email alerts
|

Maternal antioxidant treatment protects adult offspring against memory loss and hippocampal atrophy in a rodent model of developmental hypoxia

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 93 publications
(243 reference statements)
0
17
0
1
Order By: Relevance
“…Simultaneously, antioxidants prevent the shortening of dendrites, and reduction of gamma-aminobutyric acid subunit receptors in the hippocampus, thereby inhibiting the development of anxiety-like behavior in the offspring [ 54 ]. A similar mechanism explains that the cause for maternal subjects exposed to antioxidants exhibits more protective effects against memory decline and hippocampal atrophy in the offspring [ 55 ]. Hence, this explains the underlying mechanism for the high level of the recognition index demonstrated by female offspring in HYT5, HYT50, and HYT500 compared to the HS group.…”
Section: Discussionmentioning
confidence: 99%
“…Simultaneously, antioxidants prevent the shortening of dendrites, and reduction of gamma-aminobutyric acid subunit receptors in the hippocampus, thereby inhibiting the development of anxiety-like behavior in the offspring [ 54 ]. A similar mechanism explains that the cause for maternal subjects exposed to antioxidants exhibits more protective effects against memory decline and hippocampal atrophy in the offspring [ 55 ]. Hence, this explains the underlying mechanism for the high level of the recognition index demonstrated by female offspring in HYT5, HYT50, and HYT500 compared to the HS group.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, valproic acid restored neprilysin (NEP) activity and memory deficits in adult offspring rats caused by prenatal hypoxia, which involves regulating the NEP gene by binding the APP intracellular domain (AICD) to the NEP promoter ( Nalivaeva et al, 2012 ). For memory impairment in hypoxic offspring during pregnancy, it has been shown that maternal vitamin C supplementation during hypoxic gestation can prevent excessive oxidative stress in the placenta, thereby ameliorating the adverse effects of prenatal hypoxia on hippocampal tissue atrophy and memory loss in adult offspring ( Camm et al, 2021 ). Crocin significantly improves hypoxia in the brain tissue of neonatal rats during pregnancy by improving memory impairment and molecular alterations related to hypoxia ( Ghotbeddin et al, 2021 ).…”
Section: Future Prospectsmentioning
confidence: 99%
“…Although fetal cells and organs have some compensatory responses to hypoxia, they are insufficient to protect the developing brain from severe or chronic hypoxia ( Riljak et al, 2016 ; Piesova et al, 2020 ). Prenatal hypoxia decreases the number of neurons and synaptic density in the hippocampus, which also alters the release of neurotransmitters ( Chen et al, 2020 ; Camm et al, 2021 ). Prenatal hypoxia can have adverse effects on the development of the central nervous system (CNS) and may lead to future behavioral disorders.…”
Section: Introductionmentioning
confidence: 99%
“…The mechanisms underlying the effects of chronic fetal hypoxia and IUGR on epigenetic programming of the fetal brain endothelial cells or NVU has not been studied. However, the effects induced by hypoxia and oxidative stress in the fetal brain suggest the involvement of epigenetic mechanisms (Camm et al, 2021).…”
Section: Perinatal Programming Of the Nvu: Potential Epigenetic Mechanismsmentioning
confidence: 99%
“…However, brain vasodilation does not ensure normal brain development in growth-restricted fetuses, and the neurodevelopmental outcomes will depend on the timing of hypoxia, the severity of IUGR, and the gestational age at delivery (Padilla et al, 2011;Baschat, 2014). Studies in animal models have demonstrated that gestational chronic hypoxia reduces the neuronal number and vascular and synaptic numbers in the hippocampus, impairing memory function in adult rats (Camm et al, 2021). In addition, IUGR may compromise cerebral vascular homeostasis by increased excitotoxicity, oxidative stress, and neuroinflammation (Miller et al, 2016;Sweeney et al, 2019).…”
Section: Introductionmentioning
confidence: 99%